Pengedukasian Zero Waste untuk Membentuk Karakter pada Anak Usia Dini di TK Dharma Wanita 2 - Binti Azizatun Nafi’ah; Reydiva Novia Hermawan (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2024)
Quality education is one of the points in sustainable development or Sustainable Development Goals (SDG's). Good quality education must be applied to all areas, especially in villages, because it is the capital for carrying out development. However, in Musir Kidul Village, the quality of education is relatively low. So strategic efforts or steps are needed to improve the quality of education in Musir Kidul Village which is realized by providing education through outreach and teaching activities. The aim of implementing the activity is to improve the quality of education in Musir Kidul Village and create a generation that cares about the environment, the main of which is waste management. The partner invited to work together is TK Dharma Wanita 2. The method used is qualitative with data collection techniques using observation and study literature. Observations were carried out to determine the conditions and problems in the education sector in Musir Kidul Village which were carried out at Dharma Wanita Kindergarten 2. Next, a literature study was carried out using available documents such as journals, internet sites, etc. so that appropriate efforts could be determined to overcome them. problems. The results of the implementation of activities show that students who are young children have a great curiosity about zero waste and the knowledge and abilities they have are increasing. It is hoped that socialization activities will be carried out continuously with various materials for character building and the number of teaching staff at Dharma Kindergarten Female 2 can be added.